91.3k views
3 votes
Drag values to complete each equation.

Drag values to complete each equation.-example-1

2 Answers

2 votes

the answer is in the attachment below:

Drag values to complete each equation.-example-1
User Beowulf
by
5.2k points
5 votes

Answer:

1) The value of
((8^3)^48^(-9))/(8^3) is 1.

2) The value of
(8^38^(4))/((8^2)^4) is
8^((-1)).

Explanation:

Given Expressions,

1)
((8^3)^48^(-9))/(8^3) then

Using property of exponents
(a^x)^y=a^(xy)


((8)^(12)8^(-9))/(8^3)

Using property of exponents
a^xa^y=a^(x+y)


((8)^(12-9))/(8^3)


\Rightarrow ((8)^(3))/(8^3)

Using property of exponents
(a^x)/(a^y)=a^(x-y)
and
a^0=1


8^((3-3))=8^0=1

Thus, The value of
((8^3)^48^(-9))/(8^3) is 1.


((8^3)^48^(-9))/(8^3)

2)
(8^38^(4))/((8^2)^4)

Now applying property of exponents
(a^x)^y=a^(xy)
in denominator,


(8^(3)8^(4))/(8^8)

Using property of exponents
a^xa^y=a^(x+y)


(8^(3+4))/(8^8)


\Rightarrow (8^(7))/(8^8)

Using property of exponents
(a^x)/(a^y)=a^(x-y)


8^((7-8))=8^((-1))

Thus, the value of
(8^38^(4))/((8^2)^4) is
8^((-1))


User Erdos
by
6.2k points